PERBANDINGAN KINERJA REKSA DANA SYARIAH DAN REKSA DANA KONVENSIONAL - Ratnawati, Vince; Khairani, Ningrum (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2012)
his study aims to find out about 1) The performance difference Islamic mutual funds andconventional mutual funds (in terms of return and risk), 2) The difference in theperformance of Islamic and conventional mutual funds (dilihhat of Sharpe and TreynorIndex index), 3) The difference in the performance of mutual funds Islamic and conventional(as seen from Jensen Alpha). The method used in this research is descriptive method ofcomparative study of the samples determined researcher from January 2006 to December2009. The research sample is a type of fixed income funds and konvensinal sharia and Islamicmutual funds and conventional mix. Hypothesis testing is performed using different testindependent sample t-test to determine whether the two mutual funds significantly differentor not. Tool of statistical test used was the program Statistical Product and Service Solutions(SPSS) ver. 17.0 for Windows and Microsoft Excel 2007, while the data used in the form ofdata on Net Asset Value per Unit of Participation (NAV / Unit), Jakarta Islamic Index (JII)and LQ45 Index and the data rate of Bank Indonesia Certificates (SBI) and CertificateWadiah BankIndonesia (SWBI) monthly period 2006-2009. The results showed that theperformance of mutual funds, both Islamic and conventional are different, but notsignificantly. This has become one of the economic development of evidence sharia inIndonesia, particularly in the capital markets and an encouraging performance againstperlaku Islamic economics. In the business performance of Islamic mutual funds is no lessfavorable to conventional mutual funds, and religus more accountable, for carrying out aseries of processes in accordance with the principles of Shariah.Keywords: Performance, mutual funds, risk and return, Sharpe index, Treynor index, JensenAlpha